History, Agendas, and Anomalies of Bangladesh Politics - Md. Yeasir Arafat; Fahmida (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This article explores the political journey of Bangladesh from its birth in 1971 to the difficult present, like a long and winding river shaped by storms of ambition, ideology, and outside influence. After gaining independence, the country dreamed of unity, rebuilding, and democracy. But over time, those hopes were shaken by repeated waves of political instability, military rule, and weak attempts to build lasting democracy. Political agendas changed again and again, like a swinging pendulum moving between dreams of economic growth and infrastructure. Yet, these goals were often blocked by corruption, family-based control of power, and unfair elections. The story of democracy in Bangladesh has not only been written by elected leaders but also shaped by powerful unelected groups such as the military, business elites, and foreign powers. Each of them has left their mark on the country’s political path. As the nation moved between secular ideals and the rise of religion in politics, its institutions became weaker, burdened by political bias and growing public distrust. At the center of all these are deep political problems, like cracks in a building’s foundation, which have blocked the path toward a fair and fully representative democracy. This article also looks closely at these problems and shows how they still affect political choices and make it harder for Bangladesh to build a strong and stable democratic future.